Propagation of Conifers and their Importance - Sharifboyevich, Kurbanov Ibragimjon (American Journal of Biodiversity, 2025)
This Article Comprehensively Discusses the Ecological and Economic Significance of Coniferous Trees, their Environmental Impact, Species Diversity, And Propagation Methods. Based on Scientific Analysis and Practical Approaches, It Highlights The Role of Conifers in Ecosystems and the Importance of their Conservation.